Cognitive screening in substance users: Diagnostic accuracies of the Mini-Mental State Examination, Addenbrooke's Cognitive Examination–Revised, and Montreal Cognitive Assessment. Issue 2 (7th February 2018) - Ridley, Nicole; Batchelor, Jennifer; Draper, Brian; Demirkol, Apo; Lintzeris, Nicholas; Withall, Adrienne
ABSTRACT: Introduction : Despite the considerable prevalence of cognitive impairment in substance-using populations, there has been little investigation of the utility of cognitive screening measures within this context. In the present study the accuracy of three cognitive screening measures in this population was examined—the Mini-Mental State Examination (MMSE), the Addenbrooke's Cognitive Examination–Revised (ACE–R), and the Montreal Cognitive Assessment (MoCA). Method : A sample of 30 treatment-seeking substance users and 20 healthy individuals living in the community were administered the screening measures and a neuropsychological battery (NPB). Agreement of classification of cognitive impairment by the screening measures and NPB was examined. Results : Results indicated that the ACE–R and MoCA had good discriminative ability in detection of cognitive impairment, with areas under the receiver-operating characteristic (ROC) curve of .85 (95% confidence interval, CI [.75. .94] and .84 (95% CI [.71, .93]) respectively. The MMSE had fair discriminative ability (.78, 95% CI [.65, .93]). The optimal cut-score for the ACE–R was 93 (impairment = score of 92 or less), at which it correctly classified 89% of individuals as cognitively impaired or intact, while the optimal cut-score for the MoCA was <26 or <27 depending on preference for either specificity or sensitivity. The optimal cut-score for the MMSE was <29; however, this had low sensitivity despite good specificity. Conclusions : These findings suggest that the MoCA and ACE–R are both valid and time-efficient screening tools to detect cognitive impairment in the context of substance use.